Literary Texts: Classroom Interaction - Kapur, Kirti (THE PRIMARY TEACHER, 2010)
English language textbooks comprise literary pieces representing different forms of writing. These texts are informative and provide a rich reading experience as well as promote and strengthen language skills and abilities. All literary pieces belong to the realm of prose, except for poems. Prose is closer to our day-to-day experience of language as compared to poetry. Poetry represents an unconventional use of language. Therefore, it requires a different approach to teaching. A poem is often highly condensed and is more implicit than explicit. The rhythm and the flow of a poem enable us to understand and appreciate the poem without much effort. Therefore reading the poem aloud in the class is of utmost importance. Poetry is an experience more than just the use of language. Learners should be encouraged to come up with their own interpretation of poems. Literary prose pieces also make for interesting reading. Stories have a way with children. Their language is vivid and often learners identify with certain characters or relate with the situation presented. The purpose of a literary text is to make the reader appreciate it and not just to impart ‘information’. Giving a chance to learners to make inferences about characters and happenings and draw conclusions will enable them to appreciate the text.